Conduction of fluids through porous parallel walls - DEVIA NARVAEZ, DIANA MARCELA; RESTREPO PARRA, ELISABETH; MESA, FERNANDO (Scientia et Technica, 2014)
A conducting fluid is continuously injected or ejected through a pair of parallel porous walls and it escapes in both directions along the channel. The flow forms a stagnation point at the center and the effluence is restricted by a magnetic field. A theoretical analysis of steady state solutions of the MHD equations in the incompressible case is given as a function of three parameters: the Reynolds number Re, the magnetic Reynolds number Rm and Alfvenic Mach number MA for some of significant asymptotic limits.